Application of fused deposition modeling technology for fabrication jigs of three-point bending test for dental composite resins. (June 2022) - Ishida, Yoshiki; Miura, Daisuke; Shinya, Akikazu
Abstract: This study aimed to clarify the application possibility of the fused deposition modeling (FDM) technology on the fabrication of jigs for a flexural test of dental composite resins (CRs). Three types of jigs were prepared to carry out three-point bending tests; 3D printed jig including support rollers, 3D printed jig with stainless-steel support rollers, and stainless-steel jig and stainless-steel support rollers. An FDM 3D printer with polylactic acid filament was used to produce 3D printed jigs. For evaluation of flexural strength, two types, packable and flowable, of composite resins were selected to prepare specimens. Three-point bending tests were performed using a universal testing machine. Then flexural strength and flexural elastic modulus were calculated. Specimen preparation and three-point bending test were conducted according to the ISO 4049:2019. All experiments were repeated 20 times. Flexural strength and flexural elastic modulus of packable CR were significantly larger than those of flowable. However, there were no significant differences among the jigs in both results. Consequently, FDM technology could be applied to fabricate jigs for the flexural test of CRs, and the mechanical properties could be evaluated as accurately as a stainless-steel jig. Highlights: ● FDM printer was applied to fabricate jigs for flexural tests of composite resins. ● Results of flexural test with printed jig were compared with stainless-steel jig. ● No significant differences were found between printed and stainless-steel jigs.